Effects of Downstream Plasma Exposure on β-Ga2O3 Rectifiers. (3rd June 2021) - Xia, Xinyi; Xian, Minghan; Fares, Chaker; Ren, Fan; Kim, Junghun; Kim, Jihyun; Tadjer, Marko; Pearton, Stephen J.
Abstract : The effects of downstream plasma exposure with O2, N2 or CF4 discharges on Si-doped Ga2 O3 Schottky diode forward and reverse current-voltage characteristics were investigated. The samples were exposed to discharges with rf power of 50 W plasma at a pressure of 400 mTorr and a fixed treatment time of 1 min to simulate dielectric layer removal, photoresist ashing or surface cleaning steps. Schottky contacts were deposited through a shadow mask after exposure to avoid any changes to the surface. A Schottky barrier height of 1.1 eV was obtained for the reference sample without plasma treatment, with an ideality factor of 1.0. The diodes exposed to CF4 showed a 0.25 V shift from the I–V of the reference sample due to a Schottky barrier height lowering around 14%. The diodes showed a decrease of Schottky barrier height of 2.5 and 6.5% with O2 or N2 treatments, respectively. The effect of plasma exposure on the ideality factor of diodes treated with these plasmas was minimal; 0.2% for O2 and N2, 0.3% for CF4, respectively. The reverse leakage currents were 1.2, 2.2 and 4.8 μ A cm −2 for the diodes treated with O2, and CF4, and N2 respectively. The effect of downstream plasma treatment on diode on-resistance and on-off ratio were also minimal. The changes observed are much less than caused by exposure to hydrogen-containing plasmas and indicate that downstream plasma stripping of films from Ga2 O3 during device processing is a relatively benign approach.